THE METALOGENETICAL SPECIALIZATION OF METASOMATITES FORMATIONS IN THE MIDDLE PREDNIPROVIE BLOCK OF THE UKRAINIAN SHIELD - RUZINA, M.; BESTUZHEV, A.; ZHILTSOVA, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Data are given about ore-bearing of metasomatites in the Middle Predniprovie geoblock of the Ukrainian shield.